Teaching Assistant Unionization: Origins and Implications - Rogow, Robert; Birch, Daniel R. (Canadian Journal of Higher Education, 1984)
Teaching assistants are represented by unions in the majority of large universities in Ontario and British Columbia (and in one smaller Saskatchewan university). Both traditional economic motivation and social/psychological/political factors appear to have contributed to unionization. The unionized universities tend to be in urban settings, to have large graduate student enrolments and to have faced greater budgetary concerns at the time of unionization. Graduate students in those first unionized had lower incomes than others and a higher proportion enrolled in the humanities and social sciences and the discrepancy was greater between the income of students in these fields and that of students in other fields. The refusal of labour relations boards in Canada to allow the "student" relationship to invalidate an "employee" relationship contrasts with decisions of the (U.S.) National Labour Relations Board. This and the fact that Canadian public policy is generally more supportive of public sector unionization and more protective of unions during the period of organizing and negotiating a first agreement, perhaps account for the greater extent of T.A. unionization in Canada than in the U.S. Although as short-term, part-time employees, T.A. 's would seem to be unlikely candidates for unionization, T.A. bargaining is now an accepted institutional reality with collective agreement achievements to point to and dues income to draw on. Future budgetary, program and priority changes are likely to generate graduate student anxiety and trigger further T.A. unionization.